Existência e unicidade de soluções para um problema elítico singular - Viviane Mendes Magalhães (2016)
In this work we study existence, uniqueness and minimizing properties of the solutions of the following singular Dirichlet problem (...) where (...) is bounded domain of RN (N 2) with smooth boundary (..), f 0; f (...) 0 e 0 < (..) 1 < p < 1 .